2019
DOI: 10.12688/f1000research.16568.3
|View full text |Cite
|
Sign up to set email alerts
|

Financing Agriculture in Nigeria through Agricultural Extension Services of Agricultural Development Programmes (ADPs)

Abstract: The ADPs were designed in response to a fall in agricultural productivity and hence a concern to sustain domestic food supplies. The study examined “Financing Agriculture in Nigeria through Agricultural Extension Services of Agricultural Development Programmes.” It sought to ascertain the extent to which agricultural extension services of the agricultural development programmes have impacted the financing of agriculture in six selected local government areas in Edo South senatorial district, Nigeria using a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, the effectiveness of the ADPs declined significantly soon after the World Bank withdrew its sponsorship (Iwuchukwu and Igbokwe 2012;Agber, Iortima, and Imbur 2013;Issa 2013;Hamisu et al 2017). Auta and Dafwang (2010) and Inegbedion et al (2018) suggested that the state ADPs in Nigeria were classified as having weak sources of funding, while Davis, Lion, and Arokoyo (2019) argued that there has been no improvement in terms of funding because there is little or no effort to diversify the sources of funding for agricultural extension services, at either the federal or state level. Mbang (2015) showed that the state government is the major source of financing in the Cross River State agricultural sector.…”
Section: Funding Complications and Weak Diversificationmentioning
confidence: 99%
“…However, the effectiveness of the ADPs declined significantly soon after the World Bank withdrew its sponsorship (Iwuchukwu and Igbokwe 2012;Agber, Iortima, and Imbur 2013;Issa 2013;Hamisu et al 2017). Auta and Dafwang (2010) and Inegbedion et al (2018) suggested that the state ADPs in Nigeria were classified as having weak sources of funding, while Davis, Lion, and Arokoyo (2019) argued that there has been no improvement in terms of funding because there is little or no effort to diversify the sources of funding for agricultural extension services, at either the federal or state level. Mbang (2015) showed that the state government is the major source of financing in the Cross River State agricultural sector.…”
Section: Funding Complications and Weak Diversificationmentioning
confidence: 99%
“…This proposition was hatched around 1883. Ever since the unveiling of this proposition, followers of this view have expressed mixed opinions (Gatsi et al, 2019;Manyeki and Kotosz, 2017;Keho, 2017;Lawal et al, 2020;Asaleye et al, 2020;Lawal et al, 2019;Babajide et al, 2020;Olanrele et al, 2020;Aktan, 2017;Ifeyinwa, Idenyi, Chibuzor & Agbi, 2016;Eze, 2016;Salwindi and Seshamani, 2016;Dahunsi et al, 2019;Moore, 2016;Atasoy and Gur, 2016;Ampah and Kotosz, 2016;Magazzino et al, 2015;Funashima, 2015). Among early versions that propelled dichotomization of WP are that of Peacock and Wiseman (PW) (1961), Musgrave (1969), Gupta (1967), Goffman (1968), Peacock & Wiseman shared version (1967), among others; each explaining its own version of the proposition based on their scholarly standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…If we roll with these assumptions then, it is imperative that we account for all versions of these viewpoints. However, the study seeks to examine PW version of WP owing to the fact that it sees government spending as endogenously derived rather than exogenously specified in Keynesian growth proposition (Antonis, Constantinos & Persefoni, 2016;Li et al, 2020;Oladejo et al, 2020;Manyeki & Kotosz, 2016;Lawal et al, 2020;Lawal, Inegbedion & Ojeka, 2020;Abdur et al, 2012;Inegbedion et al, 2019). Moreso, the monolithic nature of Nigeria economy and strong believe that government spending is sin-quan-non to economic growth and development cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries of the world, the agricultural sector is regarded as a stimulant of economic development ( Food and Agricultural Statistics, 2004 ). There are shreds of evidence to show consistently that it is not possible for any country to successfully attain industrialized status without first achieving significant success in agricultural performance since the green revolution (investment in food production) is crucial to the industrial revolution ( Inegbedion et al ., 2020 ; as well as Inegbedion et al ., 2018 ). The “agricultural sector performance, particularly through improved productivity, is one of the major ways of reducing poverty in developing countries” ( Nebo & Ejionueme, 2017 ), which is consistent with the key macroeconomic goals of any economy and two of the United Nation’s Sustainable Development Goals: “No Hunger” and “No Poverty”.…”
Section: Introductionmentioning
confidence: 83%